2020
DOI: 10.5888/pcd17.190374
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Stakeholder Engagement: Expanding the Role of Pharmacists in Prevention of Type 2 Diabetes Through the National Diabetes Prevention Program

Abstract: What is already known on this topic? Pharmacists are well positioned and can be highly effective in providing preventive health services to patients in their communities; however, they remain underutilized as public health service providers. What is added by this report? We strategically leveraged partnerships with pharmacy stakeholders to develop resources and promotional materials tailored to the needs and values of pharmacists. Our efforts can help expand type 2 diabetes prevention services through the phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Diabetes and its determinants are epidemic in the United States, and prevention and management are of vital importance (18). To that end, Roszak and Ferreri conducted key informant interviews among pharmacy executives to identify barriers to and opportunities for implementing the National Diabetes Prevention Program (DPP) in community pharmacies (19). They concluded that realizing this opportunity will require reimbursement for pharmacists' efforts, minimal disruption of routine workflow, and understanding among patients that pharmacists can provide this program effectively.…”
Section: Collaboration Of Pharmacy With Other Health Care Agenciesmentioning
confidence: 99%
“…Diabetes and its determinants are epidemic in the United States, and prevention and management are of vital importance (18). To that end, Roszak and Ferreri conducted key informant interviews among pharmacy executives to identify barriers to and opportunities for implementing the National Diabetes Prevention Program (DPP) in community pharmacies (19). They concluded that realizing this opportunity will require reimbursement for pharmacists' efforts, minimal disruption of routine workflow, and understanding among patients that pharmacists can provide this program effectively.…”
Section: Collaboration Of Pharmacy With Other Health Care Agenciesmentioning
confidence: 99%
“…[1][2][3][4][5][6] This contribution comes, in large part, from the pharmacist's expertise in medication therapy management, but many successful pharmacist-led initiatives include an emphasis on lifestyle medicine. 2,6,7 Lifestyle medicine, including physical activity, plays a major role in chronic disease prevention and management. In addition to reducing all-cause mortality, exercise has been shown to prevent cardiovascular disease, diabetes, and metabolic syndrome.…”
mentioning
confidence: 99%
“…As a result, pharmacists are involved in various levels of diabetes prevention by leveraging partnerships with interdisciplinary stakeholders. 1 Studies report that the integration of pharmacists into diabetes prevention programs (DPPs) helps prevent the occurrence of diabetes, detect diabetes complications, and delay the deterioration of diabetesrelated complications and death. 2 The impacts of these DPPs include improved patient knowledge of diabetes and its treatment, better shared decision-making between patients and providers regarding diabetes self-care, and improved patient diabetes management skills.…”
mentioning
confidence: 99%